Evaluasi Kinerja Layanan Pengembangan Bisnis Bagi Usaha Kecil Menengah : Kasus BDS Garmen di Jakarta - Arfian Muslim; Musa Hubeis; Illah Sailah (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2006)
Business Development Service (BDS) is a non financial services entity which try to increase SME performance through market access, production process improvement, management development, financial facility and other that suitable SME’s need. BDS organization could be a private company, non government organization (NGO), government institution, industrial association, etc. The purpose of this study are to evaluate BDS performance and to find out BDS’s key success. This study is held with a survey methode by using questioner. The scope of this study is financial aspect, customer perspective, internal process and organization learn and growth. Performance evaluation uses a method of Balanced Scorecard. The result and analysis for BDS Harmoni are : (1) healthy financial aspect showed by rentability and liquidity ratio above 100%; (2) customer perspective is acknowledged by appropriateness between performance and perception, rate is 85,45%; (3) internal business process is quite good, refer to the capability of BDS to create and respond to SME’s need and the fulfillment of business plan; (4) organization learn and growth which is stated by employees satisfaction (67,5%). The key success of BDS is measured by financial utilization aspect (rentability, liquidity and solvability); customer (customer satisfaction and retention); internal process (the comparison between realization and business plan as well as a customer monitoring regularly); and organization learn and growth (employees satisfaction, active learning, organization development; individual empowerment, knowledge management and technology implementation). Score for BDS Harmoni is 1,9 or above standard from bechmarking standard.